PENGEMBANGAN MEDIA VIDEO ANIMASI MENGGUNAKAN APLIKASI CANVA SUBTEMA KERAGAMAN SUKU BANGSA DAN AGAMA DI NEGERIKU: Penelitian R&D - Dini Lestari; Nurlinda Safitri; Mira Mirawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Dini Lestari. 037118101. Learning media is one of the supporters in learning. However, in research schools the media used is not varied and digital-based. Therefore, learning needs the development of learning media so that students get varied learning media. The purpose of this research is to produce animated video media products canva theme 7 sub- themes 1 Ethnic and religious diversity in my country learning 1 in class IV SDN Bojonggede 05 Kab. Bogor. This study uses Research and Development (R&D) by applying the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data collection technique in this study used the instrument sheet used, namely a questionnaire. The product test was carried out by one media expert, one linguist, four material experts, and 25 student responses. The results of research from media, language, and material experts were declared very suitable for use by obtaining an average percentage of 93.21%. In the limited test stage, 25 students responded very well with an average percentage of 92.72% for the animation video based on Powtoon used. Based on the results of the study, it can be concluded that the animation video canva is declared very suitable to be used as a learning medium.